2023
DOI: 10.7554/elife.85980
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing precision in human neuroscience

Abstract: Human neuroscience has always been pushing the boundary of what is measurable. During the last decade, concerns about statistical power and replicability – in science in general, but also specifically in human neuroscience – have fueled an extensive debate. One important insight from this discourse is the need for larger samples, which naturally increases statistical power. An alternative is to increase the precision of measurements, which is the focus of this review. This option is often overlooked, even thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 304 publications
0
2
0
Order By: Relevance
“…Saccadic eye movement assessment, or video oculography, is a low-cost and highly precise method to measure cognitive function objectively by assessing the performance of well-described and validated tasks. [32][33][34] Such eye tracking has been widely used to study subclinical cognitive manifestations of psychiatric and neurodegenerative diseases. [35][36][37][38] In the present study, we sought to study saccadic eye movements to investigate cognitive deficits in patients with CRS and to correlate this measure with patient-reported outcome measures for cognitive function and sinonasal quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccadic eye movement assessment, or video oculography, is a low-cost and highly precise method to measure cognitive function objectively by assessing the performance of well-described and validated tasks. [32][33][34] Such eye tracking has been widely used to study subclinical cognitive manifestations of psychiatric and neurodegenerative diseases. [35][36][37][38] In the present study, we sought to study saccadic eye movements to investigate cognitive deficits in patients with CRS and to correlate this measure with patient-reported outcome measures for cognitive function and sinonasal quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that patients with CRS had greater difficulty with eye tracking tasks requiring increased cognitive load compared to more simple assessments of reaction time (e.g., the less cognitively demanding pro-saccade task). [32][33][34] To further explore whether patients with CRS may manifest dysfunction under conditions of higher cognitive demand, we analyzed the performance of patients with CRS and controls on the antisaccade and delay saccade tasks. In both of these tasks, patients with CRS performed significantly more poorly than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this advantage of eye tracking procedure, it should be noted that the effect of Affective Voice was smaller than in the first experiment and the main effect of Affective Voice was only significant in preregistered one-sided analysis. It has been shown that eye tracking data is susceptible to measurement error and therefore more powerful analyses may be required (Nebe et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For our investigation, we opted to use two ERP parameters, the fronto-central N2 and the parieto-central P3 amplitude, to quantify individual differences in the electrophysiological activity during EF tasks. It is crucial to note that these ERP measures often exhibit only low-to-moderate reliabilities, which needs to be taken into account in individual differences research (Cassidy et al, 2012;Nebe et al, 2023;Schubert et al, 2023). Accordingly, we addressed the issue of unreliable ERP components by integrating analyses of the electrophysiological measures with a structural equation modeling approach.…”
Section: Measuring Executive Functions With Electrophysiological Proc...mentioning
confidence: 99%